ANALYSIS OF FACTORS INFLUENCE IMPULSIVE BUYING - Husnayetti, H; Sestri, Ellya; Novida, Irma (Muhammadiyah International Journal of Economics and Business, 2018)
Retail business is currently showing a rapid growth. Rapid retail development has a significantimpact on sales turnover which also increased significantly, in which one source of increase in salesturnover comes from unplanned purchases or better known as impulse buying. Impulse buying canoccur due to stimulus in the department stores, which is an external stimuli. This research focuses on the influence of external stimuli such as price, promotion and customer service to impulse buying customer at Block M Square. Purposive sampling is used for sampling techniques thattakes150 respondents and multiple linear regression analysis as data analysis techniques. Fromthe results of the research analysis found that the variables such as price, promotion and customerservice have simultaneously significant effect on customer decisions in impulsive purchase. Fromthe three independent variables: Price (X1), Promotion (X2) and Customer Service (X3), it can beconcluded that the independent variable consumer service (X3) has positive effect of 0.484 to thedependent variable impulse buying (Y), the independent variable promotion (X2) has a positiveinfluence of 0.331 to the dependent variable impulse buying (Y), the independent variable price(X1) has negative influence of 0.196 to the dependent variable impulse buying (Y). The variablethat has the greatest influence on impulse buying variable is positive customer service variable(X3). Related to the results of these studies, retailers should be able to improve the ability ofshopkeepers by providing them with more detailed knowledge relevant to the offered product.